2017
DOI: 10.18632/oncotarget.21485
|View full text |Cite|
|
Sign up to set email alerts
|

PD-L1 expression heterogeneity in non-small cell lung cancer: evaluation of small biopsies reliability

Abstract: Immunotherapy with checkpoint inhibitors, allowing recovery of effector cells function, has demonstrated to be highly effective in many tumor types and represents a true revolution in oncology. Recently, the anti-PD1 agent pembrolizumab was granted FDA approval for the first line treatment of patients with advanced non–small cell lung cancer (NSCLC) whose tumors show PD-L1 expression in ≥ 50% of neoplastic cells and as a second line treatment for patients with NSCLC expressing PD-L1 in ≥1% of neoplastic cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 23 publications
3
79
3
3
Order By: Relevance
“…Indeed, responses have also been observed in patients whose tumors were classified as PD‐L1–negative . This can be due to different reasons: newly discovered biological complexity underpinning the tumor–immunity interplay, PD‐L1 expression heterogeneity, different clones, and inter‐ and intraobserver variability . Notwithstanding these limitations, the determination of PD‐L1 expression in neoplastic cells is a necessary condition for the treatment of NSCLC with pembrolizumab: initially used in a second‐line setting for NSCLC expressing PD‐L1 in at least 1% of the sample, its indication has been subsequently extended to first‐line treatment as a monotherapy in NSCLC expressing PD‐L1 in at least 50% of neoplastic cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, responses have also been observed in patients whose tumors were classified as PD‐L1–negative . This can be due to different reasons: newly discovered biological complexity underpinning the tumor–immunity interplay, PD‐L1 expression heterogeneity, different clones, and inter‐ and intraobserver variability . Notwithstanding these limitations, the determination of PD‐L1 expression in neoplastic cells is a necessary condition for the treatment of NSCLC with pembrolizumab: initially used in a second‐line setting for NSCLC expressing PD‐L1 in at least 1% of the sample, its indication has been subsequently extended to first‐line treatment as a monotherapy in NSCLC expressing PD‐L1 in at least 50% of neoplastic cells …”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the determination of PD‐L1 on histological material is mostly performed on biopsy specimens rather than surgical resections. Given the heterogeneity of PD‐L1 expression within tumors, there is often a lack of concordance between the results obtained from biopsies and those obtained from surgical resection specimens . Therefore, we investigated whether a substantial difference between cytologic smears and core biopsies (as a surrogate of diagnostic biopsies) exists in terms of reliability for PD‐L1 determination, considering whole tumor sections as the reference.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have confirmed the antitumor efficacy of PD-1 and PD-L1, which have emerged as important targets for immunotherapy. PD-1 is a type 1 transmembrane protein of the Ig superfamily [4, 7, 8], consisting of an extracellular N-terminal IgV-like domain, a transmembrane domain, and a cytoplasmic tail [4]. It engages in inhibitory signal transmission and is expressed on activated immune cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, programmed death 1/programmed cell death ligand-1 (PD-1/PD-L1) has become a popular target for immunotherapeutic blockade of co-inhibitory immune pathways [7]. PD-L1 is the major ligand of PD-1 and is expressed on a variety of cell types [8]. Importantly, PD-L1 is expressed on many tumors, including breast cancer, gastric cancer, NSCLC, pancreaticcancer, bladder cancer, cervical cancer, renal cell carcinoma,and melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…While the clinical usefulness of PD‐L1 expression as a suitable biomarker for response to treatment is clear, its predictive value is still unsatisfactory. Relevant limitations include intra‐ and inter‐tumor heterogeneity and technical issues related to the use of different mAbs and diagnostic material (cytology, diagnostic biopsies vs surgical specimens) . Thus, research in progress is focused on finding additional checkpoints to be exploited for targeting with therapeutic antibodies used alone or in combination.…”
Section: Expression Of Inhibitory Checkpoints In Nk Cells and Their Lmentioning
confidence: 99%